On The Sustainability of the EUs Current Account Deficits (2007)
In this paper, we test for the stationarity of EU current account deficits. Our testing strategy addresses two key concerns with regard to unit root panel data testing, namely (i) the identification of which members-states are stationary, and (ii) the presence of cross-sectional dependence. For this purpose, we employ a moving block bootstrap approach to the Hadri (2000) test. While there is evidence that current account sustainability applies to panels comprising EU members, this is not the case when non-EU economies are considered.